Agricultural R&D capacity and investments in the Asia–Pacific region - Beintema, Nienke M.; Stads, Gert-Jan (International Food Policy Research Institute, 2008)
Science and technology (S&T) are major contributors to food security, poverty reduction, and economic growth, as has been proven in Asia since the early-1970s through the Green Revolution in agriculture. Continuing to secure such gains, however, is becoming an increasingly complex undertaking. More than ever, quantitative data are vital for measuring, monitoring, and benchmarking the performance of agricultural S&T systems, including their inputs and outcomes. This brief reviews major institutional developments and investment and human resource trends in agricultural research and development (R&D) in 11 countries of the Asia?Pacific region. The brief draws on a set of country briefs, reports, and underlying datasets developed by the Agricultural Science and Technology Indicators (ASTI) initiative. ASTI worked with regional partners to collect detailed quantitative and qualitative information on research capacity and investment trends within agricultural R&D agencies. These data were then linked with investment and human resource data from the Chinese government and other secondary sources to provide a broader regional and global context.